جريمة الاعتداء على المال العام في الفقه والقانون النافذ في فلسطين : (The Crime of Offenses Against Public Funds in Islamic Jurisprudence and the Applicable Law in Palestine) - سليم علي الرجوب; سمير محمد عواودة (At-Tajdid - Intellectual Refereed Journal, 2026)
Abstract At a time when infringements upon public property are increasingly widespread within the state, this study seeks to highlight the penalties for offences against public property under Islamic Sharīʿah and the applicable law. The researchers employ a descriptive approach and adopt a comparative methodology to examine the relationship between Islamic law and the prevailing legal framework in Palestine with the aim of preventing violations of public property, and to identify the most effective means of achieving this objective. The study addresses the conceptual definitions of its key terms and the various forms of assault on public property, demonstrating the extent of convergence between Sharīʿah and positive law in defining the notion of crime, as well as the degree of consistency between Islamic jurisprudence and statutory law in clarifying the concept of public property and establishing criteria for distinguishing it from private property. It further examines the responsibility for safeguarding public property and the penalties imposed for offences against it by identifying the parties responsible for its protection and outlining the prescribed punishments in both Islamic jurisprudence and law. The study concludes that assaults on public property take multiple forms, including theft, embezzlement, breach of trust, negligence in the performance of duties, and the misuse of public property for personal purposes, and further affirms that Islamic Sharīʿah prescribes eschatological punishments for such offences, a feature that renders it more comprehensive than positive legal systems. Keywords: crime; public property; assault; Islamic jurisprudence and law..